FluTracking: Weekly online community-based surveillance of respiratory illness in Australia, 2023 Report - Kerr, Alexandra; Kerr, Sandra; Adams, Stuart; McKenzie, tom; Boettiger, David; Dalton, Craig (Communicable Diseases Intelligence, 2025)
FluTracking Australia, an online respiratory illness surveillance system, monitors self-reported symptoms, care-seeking, absence from normal duties, and testing and vaccination for influenza and coronavirus disease 2019 (COVID-19). From 2022 to 2023, the number of participants who completed at least one survey decreased by 16.8%, possibly due to participation fatigue and additional survey questions. In 2023, FluTracking identified a 22% reduction in the peak weekly incidence of fever and cough (FC) compared to the 2022 season. The 2023 FC peak was similar in timing to the 2022 FC influenza peak but smaller in magnitude compared to most previous years documented by FluTracking. From 2022 to 2023, FluTracking observed: A 36% decrease in influenza polymerase chain reaction (PCR) testing among participants reporting incident FC symptoms, largely influenced by a 57% decrease in New South Wales. A 25% decrease in SARS-CoV-2 testing, by PCR and/or rapid antigen test (RAT), among participants reporting incident runny nose and sore throat (RNST) symptoms. An 11% decrease in SARS-CoV-2 testing (PCR and/or RAT) among participants reporting incident FC symptoms. Reduced testing accessibility coupled with modified testing practices likely contributed to these decreases. By June 2023, SARS-CoV-2 PCR testing rates among participants with incident FC symptoms aligned with influenza PCR testing rates. Period cumulative incidence of RNST symptoms showed minimal variation across age groups in 2023. In contrast, FC period cumulative incidence inversely correlated with age, suggesting young individuals experience a higher cumulative incidence of FC symptoms.